Readiness of health posts to manage child wasting in six districts of Ethiopia - Alinoor Mohamed Farah; Samson Gebremedhin; Beshada Rago; Aweke Kebede; Kemeria Barsenga; Tafara Ndumiyana; Tayech Yimer; Hiwot Darsene; Shibru Kelbessa; Beza Yilma; Seifu Hagos Gebreyesus (PLoS ONE, 2025)
Background Service readiness is essential for providing effective health services. Adequate infrastructure, trained staff, and essential commodities must be in place to enable timely diagnosis and treatment, without which improvements in child survival cannot be achieved. Objective To assess the readiness of health posts to manage child wasting in six selected districts. Data and methods A facility-based cross-sectional survey was conducted in April 2023 to assess the readiness of 72 randomly selected health posts in six districts. A composite index was developed using a weighted additive approach to assess the availability and readiness of severe acute malnutrition (SAM) and moderate acute malnutrition (MAM) services. Readiness scores were defined as the weighted mean of the availability of basic amenities, staff and guidelines, equipment and medicine, and nutritional commodities. Descriptive statistics were used to report the availability of tracer items, and the second (median) and third quantile regression models were used to analyze the association between independent variables. Results The overall SAM and MAM readiness scores were 57.9% and 53.9%, respectively. Basic amenities scored the lowest (45.8% for both) owing to limited electricity (40.3%) and water access (51.4%). Staff and guideline readiness was 66.7%, with highly trained staff (88.9%) and registration/follow-up cards (90.3% SAM; 86.1% MAM), but low growth charts (11.1%) and IYCF aids (47.2%). The availability of equipment was 60.3% for SAM and 64.6% for MAM, with high MUAC tapes (97.2%) and scales (83.3%), but low timers (16.7%). The availability of medicines and commodities scored 67.1% for SAM and 69.0% for MAM, with RUTF/RUSF (79.2% SAM; 59.7% MAM) and vitamin A (77.8%); gaps remained for antibiotics (55.6%), zinc (61.1%), and IFA tablets (58.3%). Only 19.4% of facilities met the ≥ 75% readiness for SAM, compared with 11.1% for MAM. Conclusion In conclusion, improving wasting service readiness requires strengthening basic infrastructure, ensuring reliable supply chains, and investing in training and supervision to build MAM capacity. The wide variation in facility preparedness highlights the need for context-specific approaches, with tailored support for remote and crisis-affected areas to achieve effective integration of MAM services into primary health care.